The Crisis Management Leadership Style of Mayor Bima Arya during the Covid-19 Pandemic - Irma Nur Atikah*; Ahmad Chumaedy; Toddy Aditya; Erik Syehabudin (Universitas Syiah Kuala, 2023)
This study aims to examine how big the mayor Bima Arya’s Crisis Management Leadership Style is in the Covid-19 pandemic perod. The Method used in this Study is a descriptive – qualitative Metode. The purpose of using this Method is to find out how big the mayor Bima Arya’s Crisis Management Leadership Style is in the Covid-19 pandemic perod